2021
DOI: 10.1002/1878-0261.12969
|View full text |Cite
|
Sign up to set email alerts
|

Tumour‐derived substrate‐adherent cells promote neuroblastoma survival through secreted trophic factors

Abstract: Neuroblastoma (NB) is the most common extracranial solid tumour in children. NB is highly heterogeneous and is comprised of a mixture of neuroblastic cancer cells and stromal cells. We previously reported that N-type cells (neuroblastic cells) and S-type cells (substrate-adherent cells) in the SK-N-SH cell line shared almost identical genetic backgrounds. Sublines of N-and S-type cells were isolated from an early passage (P35) of SK-N-SH. Sequencing analysis revealed that all sublines harboured the anaplastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…Importantly, we found that the 5hmCH-containing cell-specific gene set of hypoxic BE(2)-C and, preferentially, the gene sets of LA1-5s cells, which both display MES/NCC-like characteristics, showed associations with poor survival of NB patients. Although the abundance of the fibroblast-like S cells in NB tumors suggests more favorable disease prognosis (Mora et al, 2001), we assume that migratory abilities of the nontumorigenic S-type LA1-5s might enhance invasive behavior of NB cells, similarly as recently shown for S-type cells that could promote viability of N cells (Li et al, 2021).…”
Section: Discussionsupporting
confidence: 60%
“…Importantly, we found that the 5hmCH-containing cell-specific gene set of hypoxic BE(2)-C and, preferentially, the gene sets of LA1-5s cells, which both display MES/NCC-like characteristics, showed associations with poor survival of NB patients. Although the abundance of the fibroblast-like S cells in NB tumors suggests more favorable disease prognosis (Mora et al, 2001), we assume that migratory abilities of the nontumorigenic S-type LA1-5s might enhance invasive behavior of NB cells, similarly as recently shown for S-type cells that could promote viability of N cells (Li et al, 2021).…”
Section: Discussionsupporting
confidence: 60%